Isu-Isu Kebijakan Publik Kontemporer - Bambang Supriyono (Public Inspiration : Jurnal Administrasi Publik, 2020)
Public policy issues are part of a very important stage of the policy process. The selection of the right issue among the existing issues will determine or be able to leverage (leverage) the resolution of complex public problems and require systemic resolution. There are several dimensions for sorting out contemporary policy issues, namely issues concerning the policy substance and issues concerning the policy process; both can become strategic issues when studied based on the substance of policies, actors, resources, situation specifications, and actors' authority to set strategic issues into the policy agenda. One important approach in analyzing public policy issues is the deliberative policy approach, an approach that promotes dialogue between interested parties to obtain certainty about strategic policy issues.